Facile synthesis of highly thermally stable nanoporous γ-aluminas from aluminum alkoxide precursors1. Issue 61 (4th July 2015) - Mohammadnezhad, Gholamhossein; Akintola, Oluseun; Plass, Winfried; Schacher, Felix H.; Steiniger, Frank; Westermann, Martin
<x xml:space="preserve">Abstract</x> The effects of aluminum alkoxide single source precursors on the sol–gel synthesis of highly thermally stable nanostructured alumina by nonionic triblock copolymer P123 were investigated.